Unusual magnetic behavior of TiO2-doped CuFeO2 crystals (CuFe1−xTixO2) grown by the optical floating zone method. Issue 15 (24th March 2023) - Hou, Jingwen; Goodman, Bernard A.; Lu, Yuchen; Zhang, Qunyue; Huang, Bin; Chen, Long; Xu, Shoulei; Deng, Wen; Xiong, Dingkang
Abstract : Crystals of synthetic delafossite with greatly affected magnetic properties can be prepared by doping with a limited range of Ti contents. Abstract : Synthetic Ti-doped delafossite (CuFe1− x Ti x O2 ) was prepared by solid state reaction of Fe2 O3, CuO and TiO2, and crystals were successfully prepared by the optical floating zone method using a modified experimental protocol that produced crystals in <10% of the time used in previous work. The effects of Ti on the microstructure and magnetic properties of CuFeO2 were investigated. The nonlinear change of cell size may be the result of Ti 4+ reduction to Ti 3+ . However, the Fe oxidation state was not affected by Ti doping, although some oxidation of Cu + to Cu 2+ was observed with the highest Ti contents. The two characteristic magnetic transition temperatures of CuFeO2 occurred at 17 K ( T N1 ) and 11 K ( T N2 ) in the undoped crystal, and these increased to 51 K and 20 K, respectively, in the crystal with x = 0.007, although there was no major change in the two magnetic transition temperatures in crystals with other doping concentrations. In an applied magnetic field of 500 Oe, the magnetization of the x = 0.007 sample was 22 times that of CuFeO2, and its magnetization curve shows the coexistence of regions with ferrimagnetic and antiferromagnetic properties. Furthermore, magnetic hysteresis loops revealed that the saturation magnetization ( M ) of the sample x = 0.007 is 4.15 emu g −1, but at higher Ti concentrations the M – H curves returned to pairwise linear temperature dependence. Overall, crystals of synthetic delafossite with greatly affected magnetic properties can be prepared by doping with a limited range of Ti contents.